Association between psychiatric symptoms with multiple peripheral blood sample test: a 10-year retrospective study - Qiu, Jianqing; Yu, Cheng; Kuang, Yalan; Hu, Yao; Zhu, Ting; Qin, Ke; Zhang, Wei (Frontiers in Psychiatry, 2024)
BackgroundPsychiatric illness is thought to be a brain somatic crosstalk disorder. However, the existing phenomenology-based Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) diagnostic framework overlooks various dimensions other than symptoms. In this study, we investigated the associations between peripheral blood test indexes with various symptom levels of major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia (SCZ) to explore the availability of peripheral blood test indexes.MethodsWe extracted cases diagnosed with MDD, BD, and SCZ at West China Hospital from 2009 to 2021, translated their main complaints into Research Domain Criteria (RDoC) symptom severity scores using nature language processing (NLP), and collected their detailed psychiatric symptoms and peripheral blood test results. Then, generalized linear models were performed between seven types of peripheral blood test values with their transformed RDoC scores and detailed symptom information adjusted for age, gender, smoking, and alcohol history.ResultsSeveral inflammatory-related indexes were strongly associated with the negative valence system (NVS) domain (basophil percentage adjusted β = 0.275, lymphocyte percentage adjusted β = 0.271, monocyte percentage adjusted β = 0.223, neutrophil percentage adjusted β = −0.310, neutrophil count adjusted β = −0.301, glucose adjusted β = −0.287, leukocyte count adjusted β = −0.244, NLR adjusted β = −0.229, and total protein adjusted β = −0.170), the positive valence system (PVS) domain (monocyte percentage adjusted β = 0.228, basophil count adjusted β = 0.176, and glutamyl transpeptidase adjusted β = 0.171), and a wide range of mood, reward, and psychomotor symptoms. In addition, glucose, urea, urate, cystatin C, and albumin showed considerable associations with multiple symptoms. In addition, based on the direction of associations and the similarity of symptoms in terms of RDoC thinking, it is suggested that “positive” mood symptoms like mania and irritability and “negative” mood symptoms like depression and anxiety might be on a continuum considering their opposite relationships with similar blood indexes.LimitationsThe cross-sectional design, limited symptoms record, and high proportion of missing values in some other peripheral blood indexes limited our findings.ConclusionThe proportion of high inflammatory indexes in SCZ was relatively high, but in terms of mean values, SCZ, BD, and MDD did not differ significantly. Inflammatory response showed a strong correlation with NVS, PVS, and a range of psychiatric symptoms especially mood symptoms, psychomotor symptoms, and cognitive abilities.